(untitled) (Global Journal of Science Frontier Research, 2012)
This study was conducted to examine urban-rural migration in Delta State, Nigeria and its implication for extension service. Data were collected from 180 respondents who were purposively selected. It was discovered that most of the migrants were males, mostly in the age range of 50 years and above; mostly married and had one form of formal education or the other; had average household size of 6 persons. Most of them have spent 6-10years in the rural area and their migration was mostly prompted by retirement. The selected socio economic variables of the migrants had significant relationship with the decisions of the migrants to engage in agricultural activities. Implications of the findings for extension service include identifying and training the migrants on the current skills and technologies of agriculture, taking advantages of their level of exposure to make them opinion leaders and identifying them a year to their retirement and giving them training in agricultural enterprise of their choice for their post retirement life.